Modeling the dynamics of gear system provided the value of equality of the rigidity of the bearings - Тимченко, Анатолій Анастасійович; Охріменко, Карл Якович; Дяченко, Петро Васильович (Eastern-European Journal of Enterprise Technologies, 2012)
The modification of the basic mathematical model of the dynamics of a single-stage gear system, in the case of equal values ​​of the rigidity of the bearings is proposed. The basic and the modified mathematical model with the appropriate identifier table is shown